2018
DOI: 10.1111/jwas.12563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stocking density and feeding regime on larval growth, survival, and larval development of Japanese flounder, Paralichthys olivaceus, using live feeds

Abstract: This research examined the effect of initial stocking density and feeding regime on larval growth and survival of Japanese flounder, Paralichthys olivaceus. Larval rearing trials were conducted in nine 50‐L tanks with different initial stocking densities combined with different feed rations (20 larvae/L with standard feed ration [LD], 80 larvae/L with standard feed ration [HD], and 80 larvae/L with four times the standard feed ration [HD+]). Larvae were stocked on 0 days posthatch (DPH) following hatching of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…High stocking densities in larviculture promote increases in nitrogen residue, degrading the water quality and affecting fish growth. Conversely, reduced numbers of fish in the tank means underused space, causing economic loss to the fish farmer (Geng et al, 2019; Luz & Santos, 2008; Sahoo et al, 2010). Also, inadequate feeding rate and frequency cause reduced fish growth and poor water quality (Couto et al, 2018; Okomoda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…High stocking densities in larviculture promote increases in nitrogen residue, degrading the water quality and affecting fish growth. Conversely, reduced numbers of fish in the tank means underused space, causing economic loss to the fish farmer (Geng et al, 2019; Luz & Santos, 2008; Sahoo et al, 2010). Also, inadequate feeding rate and frequency cause reduced fish growth and poor water quality (Couto et al, 2018; Okomoda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to prevent losses from disease during the larval rearing period, as well as reduce labor costs associated with flounder seed stock production, have led to the advent of larviculture methods such as the hottoke-shiiku, or "stagnant water" method, which aims to establish a more stable bacterial community in the rearing environment (Tomoda, Shigeki, Bullet, & Nakamura, 2011). Intensification efforts have also resulted in improvements of larval rearing production of this species, allowing for increased seedstock production in smaller volume tanks (Geng et al, 2019). The larval rearing of olive flounder typically follows a "standard" marine finfish regime of enriched rotifers (Brachionus sp.)…”
Section: Overview Of Olive Flounder Aquaculturementioning
confidence: 99%
“…After collection, either embryos are stocked into incubation tanks for hatching at densities of 200-400 embryos/L or embryos can be stocked directly into larval rearing tanks at desired rearing densities, which can range from 10 to 80 larvae/L depending on the level of intensity of the larval rearing system. Experimental trials have indicated that higher density larval stocking densities may offer improved production, as long as food supply and water quality conditions are maintained at sufficient levels (Geng et al, 2019). Larval rearing tanks vary in size, configuration, and operation, with rearing techniques adapted for each unique situation.…”
Section: Overview Of Olive Flounder Aquaculturementioning
confidence: 99%
“…An annual aquaculture production of olive flounder in Korea increased sharply from 1,037 metric tons in 1990 to 37,269 metric tons in 2018 (KOSIS, 2019). This species was recently introduced into the United States and Turkey for commercial production (Geng et al., 2019).…”
Section: Introductionmentioning
confidence: 99%